TRANSFORMATION FROM THE EDGE; ORGANIZATIONAL CHANGE MANAGEMENT BASED ON ISLAMIC CULTURE IN PESANTREN - Romli, Mustain; Syamweil , Faizin (Universitas Nurul Jadid, 2022)
This study analyzes change management based on Islamic culture at the Nurul Jadid Islamic Boarding School. This study uses a qualitative case study type method. Data collection techniques using interviews, observation, and documentation. The results showed that the stages of change management carried out by Pesantren Nurul Jadid based on the perspective of Kurt Lewin, among others: first, at the Unfreezing stage (review or survey, particular direction from the leadership to subordinates), mapping the potential of each human resource, motivation). The second is the Changing stage (socialization, seminars, training). The third is the Refreezing stage (creating a new culture or condition, cooperation, commitment, and evaluation).